Procurement of Power for Medium Term Model Agreement - Planning Commission (Planning Commission, 2014)
Development of a framework that can enable distribution utilities and power producers to enter into medium-term contracts for supply of electricity is essential for utilising available capacity at competitive prices. For this purpose, utilities and power producers would need to enter into medium-term agreements for dedicating the agreed capacity for supply of electricity to such utilities. The Central Government has already published model agreements for long-term supply of power. A similar model agreement would be required for entering into medium-term contracts.
Planning Commission Government Of India
Planning Commission Government of India